President’s Message - Mushayandebvu, Barbara (Operating Room Nurses Association of Canada Journal, 2017)
What an awesome conference for ORNAC’s 25th National in Niagara. From the education sessions that inspired and provided continuing education, to the social events that had everyone networking and dancing, this conference will go down in history as one of the best conferences yet. I hope those who were able to attend have great memories and have shared their experiences with those who held down the fort to enable us to attend. Thank you to the 2017 Conference Planning Committee for a job well done.